Social technologies on small farms: A case study in Brazil - Scalco, A. R. [UNESP]; Rotolli, J. A. [UNESP] (My University, 2013)
There are many challenges to be faced by small farmers in Brazil: technological; financial and management . And in this context in which is discussed the importance of developing social suitable alternative technology. The small farmer needs to survive in its activity in a sustainable way, but also needs this activity to bring increasing productivity and profitability. Therefore, this research presents an analysis of the possibilities of development of social technologies on small farms as well as understand the factors that trigger the development of social innovations.
Keywords: Agribusiness.; Small farms; Social technology